Exploring the Readability of Terms of Service of Social Networking Sites - Manasseh Jonah Bangmarigu, William Kodom Gyasi & (Covenant Journal of Informatics and Communication Technology, 2020)
Terms of service of social networking sites provides relevant information for end-users to make inform decision regarding their use of social networking site. The purpose of this paper was to evaluate the readability of the top five social networking sites namely Facebook, WhatsApp, Messenger, YouTube, and WeChat. Using Flesch reading ease and grade level indexes, the authors measured the readability of the selected terms of service. Measures of central tendencies, and one-way analysis of variance, with bootstrapping, were used to analyse the data. The results showed that the ToS were difficult to read when compared to the standard score of public documents. Moreover, the readability levels of the ToS required end users to have attained at least 13 years of formal education, which is equivalent to first year college student, in order for the users to find the ToS readable. In addition, no statistical difference existed among ToS of the five social networking sites meaning all the ToS of the five networks were unilaterally difficult for the average reader (end user). It is recommended that the ToS of these networks be revised to make them more readable since substantial number of their audience are young with low number of years of education.